BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN OBESITAS SENTRAL - Rofiqoh, Rofiqoh; Setyowati, Tutik; Yuska, Defniwita; Sendra, Eny (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Overweight and obesity are conditions of abnormal or excessive accumulation of body fat, which can pose various health risks. Factors that influence the occurrence of central obesity are very complex, and one of the main ones is the intake of energy and macronutrients consumed. The purpose of the study was to determine several factors associated with the incidence of central obesity. The research design used in this study was cross sectional. The research was conducted in July 2023 in Rawa Buaya Village, Cengkareng District, West Jakarta City. The population is all people of productive age. The sample amounted to 66 respondents. The sampling technique used simple random sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between energy intake (p value: 0.000) and there was no relationship between physical activity (p value: 0.366) on the incidence of central obesity. It is recommended that respondents need to check abdominal circumference regularly, especially in adulthood as screening and prevention of the risk of hyperglycemia and other NCDs.Keywords: Physical Activity, Energy Intake, Central Obesity.